WhatsApp-based complementary feeding education and counselling for adolescent mothers: A one-group pre-post study - Tisa Salma Muthi'ah; Riris Andono Ahmad; Digna Niken Purwaningrum (Journal of Community Empowerment for Health, 2022)
More than two-thirds of deaths in children are related to improper feeding practices, especially in adolescent mothers, with very low levels of complementary feeding knowledge, less responsiveness, and few skills of proper feeding practices.  The area of Banguntapan III Public Health Center (PHC) has the highest prevalence of adolescent mothers in 2018-2019. The aim of this study was to evaluate the effect of WhatsApp-based complementary feeding education and counseling for adolescent mothers who have children aged 6-24 months at Banguntapan III PHC on complementary feeding knowledge and practice. A quasi-experimental with one group pre-post test was conducted (n=10 adolescent mothers) on February-May 2021 at the Banguntapan III PHC area. The education program was conducted by trained cadres for 8 days through the WhatsApp group, then followed by asynchronous counseling once through WhatsApp private chat. Change of outcome was tested using independent sample T-test and McNemar test. The range of adolescent mothers’ age in this study was 19-20 years, with education level of junior high school (50%), and do not work (80%). The results showed that WhatsApp-based education and counselling had a significant effect on increasing the adolescent mother's IYCF knowledge (Δ = 1.1 ± 2.28) with a p-value of 0.017 < a (0.05). Meanwhile, the effect of the intervention on the IYCF practice by adolescent mothers was not significant, with a p-value of 0.311 > a (0.05). In conclusion, WhatsApp-based education and counselling for adolescent mothers can increase their level of complementary feeding knowledge, but was not been able to improve their feeding practices for infants/children aged 6-24 months.